The Relationship Between Time Perspective and Dispositional Mindfulness with Respect to Well-Being: A Systematic Review of Cross-Sectional Studies - Erguler, Hasan; Ferreira, Nuno; Adonis, Marios; Koushiou, Maria (Springer, 2023)
ObjectivesResearch on the effects of time perspectives and dispositional mindfulness on psychological well-being can be potentially insightful. However, time perspective and dispositional mindfulness constructs have mostly been studied separately, leaving room for discussion regarding their interactions. There is, so far, a limited number of empirical studies and no systematic review on this area of research. This systematic review thus aimed at providing an informative outline.MethodKey databases including Scopus and Web of Knowledge were screened, and the most recent search was conducted in June 2023. Initially, 593 entries were found to meet the criterion of cross-sectional design. Final analysis incorporated the narrative synthesis strategy for resulting 16 eligible articles.ResultsDispositional mindfulness is closely related to a flexible shift in time perspectives, called the balanced time perspective. In general, dispositional mindfulness was found to positively correlate with an optimistic view of both the past and the future, and it was also positively linked to savoring the present moment experiences. Furthermore, a non-judgmental focus is central to mindful decentering when being attentive to the actual characteristics of present stimuli.ConclusionsThe balanced time perspective is an important construct possibly linking dispositional mindfulness and time perspectives. The present-eudaimonic perspective, self-compassion, and decentering are variables that can further help guide research in outlining complex interactions that also relate to psychological well-being. Future research is advised to include longitudinal and experimental designs for a more comprehensive understanding of relevant interactions.PreregistrationThis study was preregistered to PROSPERO with the number CRD42021241388.
Keywords: Dispositional mindfulness; Balanced time perspective; Psychological well-being; Cross-sectional studies